Numerical optimization on thermal performance characteristics of interior walls based on air-conditioning intermittent running. (September 2018) - Meng, Xi; Hu, Wentao; Cao, Ying; Huang, Yisheng; Du, Junfei; Gao, Yanna
Abstract: When the air-conditioning runs intermittently, there may be the large temperature differences of the indoor air in two adjacent rooms due to the air-conditioning different running behaviors. Under this condition, a lot of the cold quantity was lost through interior walls and then the large cooling load was formed by interior walls. Aimed to this, six typically-employed interior walls were built to compare their thermal performance characteristics under air-conditioning intermittent running. The heat transfer model was built by the finite volume method and verified by the experimental data. The numerical results showed that the air-conditioning running behavior in the adjacent room had an observable influence on temperature response rates and heat flow values in inner surfaces. Compared with the solid brick walls, the daily cooling load formed by interior walls can be reduced by 26.1% for the foamed concrete wall and 12.7% for the hollow brick wall, respectively. When the temperature environment in the adjacent room was beneficial to improving the thermal response rate of the interior wall, the thin wall was the reasonable choice and whereas, the thick wall was the reasonable one.